Solvent Extraction of Test Plasmas for Improved Recovery of Lupus Anticoagulant Activity - Exner, Thomas; Papadopoulos, George; Sahman, Nilgun; Koutts, Jerry (Thrombosis and Haemostasis, 1990)
Phospholipid procoagulant material mainly derived from platelets interferes or “bypasses” the more specific tests for lupus anticoagulants. Such material in test plasmas can be inactivated with recovery of lupus anticoagulant activity by simple extraction with chloroform. This solvent treatment damages mainly factors VIII, V, VII and IX. Ether and various other solvents were less damaging to these clotting factors but not quite as effective as chloroform in the recovery of lupus anticoagulant activity.